Feminism Misread: : The Ideological Distortions Behind the Hostile Perceptions of a Good Cause - MOHANTY, Suman; OSONDU-OTI, Adaora; SUNDARAY, Sankalp (The Gender Truth Journal, 2026)
Hostile readings of feminism recast a movement for gender equality as a threat to cultural order. This article theorises ideological distortion as the systematic appropriation of feminist language while neutralising its transformative content. Using a comparative lens on Nigeria and India, it identifies three recurrent mechanisms: reframing (religious hermeneutics that substitute equality with complementarity), cooptation (state, public-health, and educational bureaucracies that deploy feminist vocabulary to extend surveillance and control), and filtration (platform, curricular, and media systems that permit circulation only when discourse aligns with dominant ideology). Empirically, Nigerian opposition concentrates among younger, educated urban men facing status anxiety who mobilise customary law and Islamic jurisprudence to delegitimise feminist demands, whereas Indian resistance is diffuse and institutional—Hindu-nationalist and bureaucratic actors accommodate feminist slogans while constraining embodied autonomy, especially around reproduction and maternal health. Across both sites, gender stereotypes, nationalist narratives, and religious authority operate as discursive gatekeepers that render feminism visible yet toothless. We propose a transferable analytic matrix - defence mechanisms, ideological justifications, institutional manifestations, public discourse effects, and impacts on women’s agency to explain how meaning itself becomes the battleground between liberation and control. The study links threat perception and hegemonic maintenance to sociotechnical infrastructures of discourse, clarifying why distortions persist despite expanded digital visibility. Normatively, it argues for counter-hermeneutics grounded in indigenous and subaltern epistemologies, intersectional coalition building that resists competitive victimhood, and accountability frameworks that audit state and platform practices for “appropriative compliance” (the use of feminist language to entrench patriarchy). By mapping how feminist claims are recoded within religious, nationalist, and bureaucratic grammars, the article reframes “feminism misread” as a predictable product of power rather than a misunderstanding and delineates strategic pathways to re-secure semantic autonomy, institutional leverage, and material gains for gender justice.